Improving access to cardiac rehabilitation for remote Indigenous clients - Frank Shepherd; Kristine Battye; Elizabeth Chalmers (Elsevier, 2003)
Abstract Objective: To identify barriers to Indigenous patients taking up a rural general practice‐based cardiac rehabilitation program. We investigated the accessibility and appropriateness of the program and the role of Indigenous health workers (IHWs) in caring for Indigenous cardiac patients. Methods: A cross‐sectional survey of knowledge and views relating to cardiac rehabilitation was undertaken with 47 Indigenous cardiac patients and 41 health professionals in remote Queensland. Results: Only three patients were fully engaged in the program. Reasons for non‐participation included: lack of knowledge about rehabilitation, low income, and having a large extended family. Although the program incorporated a training component for IHWs covering prevention and follow‐up, most did not monitor patients specifically for their heart problems and thought they did not have adequate skills. Shared care was occurring in some settings but without the participation of IHWs. Conclusions: There was general agreement that IHWs do have a role in cardiac rehabilitation. There is a need for ongoing in‐service education or inclusion in training programs. Lack of understanding of the role of IHWs is a barrier to shared care. Cardiovascular disease needs to be addressed as part of the raft of chronic illnesses. Implications: Training about chronic illnesses and their management needs to be linked to structural adaptations in the delivery of health services to allow efficient use of each professional's skills. Clear role delineation needs to be negotiated to allow all health professionals to carry out their job effectively.